Aromatherapy, massage and reflexology: A systematic review and thematic synthesis of the perspectives from people with palliative care needs. (July 2019) - Armstrong, Megan; Flemming, Kate; Kupeli, Nuriye; Stone, Patrick; Wilkinson, Susie; Candy, Bridget
Background: Effectiveness evidence of complementary therapies in people with advanced disease is uncertain, and yet people are still keen to engage in complementary therapy. Insights into people's experiences of complementary therapy in palliative care, the perceived benefits, and how they want it delivered, can inform clinical guidelines and suggest ways to test therapies more appropriately in future evaluations. Aims: Explore in people with advanced disease (1) the experiences and perceptions of benefits and harms of aromatherapy, massage, and reflexology and (2) how they would like these therapies delivered. Design: A systematic review and thematic synthesis of qualitative studies. Database search terms were related to palliative care, aromatherapy, reflexology and massage. Citations and full texts were reviewed independently against predefined inclusion criteria. Studies were appraised for quality. This review is registered at PROSPERO (22/11/2017 CRD42017081409). Data sources: MEDLINE, EMBASE, PsycINFO, AMED, CINAHL, KoreaMed and ProQuest with a bibliography search to June 2018. Results: Five qualitative studies in advanced cancer were identified. Three analytical themes were identified: (1) Experience during the therapy (enhanced well-being and escapism), (2) beyond the complementary therapy session (lasting benefits and overall evaluation), and (3) delivery of complementary therapy in palliative care (value of the therapist and delivery of the complementary therapy). Conclusions: People with advanced cancer experience benefits from aromatherapy, reflexology and massage including enhanced well-being, respite, and escapism from their disease. Complementary therapy interventions should be developed in consultation with the target population to ensure they are delivered and evaluated, where feasible, as they wish.